1992
DOI: 10.2307/2409854
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Defenses against Avian Brood Parasitism in Sympatric and Allopatric Host Populations

Abstract: The brown-headed cowbird (Molothrus ater) is a widespread, obligate brood parasite of North American passerine birds. In southern Manitoba, where hosts are sympatric with cowbirds, American robins (Turdus migratorius) ejected parasitic eggs from all experimentally parasitized clutches (N = 25) and no eggs were accepted for more than four days. In contrast, robins in northern Manitoba, an area where cowbirds do not breed, accepted parasitic eggs in 33% of nests (N = 18) for at least five days. Acceptance of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 12 publications
3
101
0
Order By: Relevance
“…However, Møller and Soler (2012) recently reviewed the literature on consistency in host responses to brood parasites and found large intraspecific variation in resistance in several host species (Cruz and Wiley 1989;Nakamura 1990;Soler 1990;Soler and Møller 1990;Briskie et al 1992;Lindholm 1999;Soler, Martínez, et al 1999;Moskát et al 2002;Martín-Gálvez et al 2006Moskát et al 2008;Stokke et al 2008;Avilés et al 2011;Soler et al 2011;Langmore et al 2012). These studies indicate that speciesspecific consistency in resistance is far from the rule.…”
Section: Introductionmentioning
confidence: 99%
“…However, Møller and Soler (2012) recently reviewed the literature on consistency in host responses to brood parasites and found large intraspecific variation in resistance in several host species (Cruz and Wiley 1989;Nakamura 1990;Soler 1990;Soler and Møller 1990;Briskie et al 1992;Lindholm 1999;Soler, Martínez, et al 1999;Moskát et al 2002;Martín-Gálvez et al 2006Moskát et al 2008;Stokke et al 2008;Avilés et al 2011;Soler et al 2011;Langmore et al 2012). These studies indicate that speciesspecific consistency in resistance is far from the rule.…”
Section: Introductionmentioning
confidence: 99%
“…Robins are a suitable study species in that they are one of fewer than 30 documented cowbird host species to eject cowbird eggs at rates above 75% (Briskie et al, 1992;Peer and Sealy, 2004), allowing for the testing of specific sensory hypotheses mediating egg rejection in this system. Previous work on this species pair showed that natural and model cowbird eggs are perceptually distinct from natural (conspecific) robin eggs: natural parasite eggs are rejected from 100% of experimental nests, whereas conspecific natural and model robin eggs are not rejected (Briskie et al, 1992;Croston and Hauber, 2014a;Rothstein, 1982;Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to either recognition or rejection, gene flow between parasitized and unparasitized populations could result in imperfect adaptations on a local level, and hence intermediate egg rejection rates (Briskie et al, 1992;Davies and Brooke, 1989). Alternatively, hosts may lag behind the parasites in the coevolutionary arms race such that the alleles for egg recognition or rejection have not completely swept through the population (Davies, 1999;Hosoi and Rothstein, 2000;Rothstein, 1990;Takasu, 1998).…”
Section: Discussionmentioning
confidence: 99%